A conceptual model for assessing blog-based learning system success in the context of business education. Issue 3 (November 2016) - Wang, Yi-Shun; Li, Ci-Rong; Yeh, Ching-Hsuan; Cheng, Shin-Tzu; Chiou, Chei-Chang; Tang, Yu-Cheng; Tang, Tzung-I
Abstract: With the proliferation in the use of blogs in educational contexts, a better understanding of how to promote university students' learning performance using blog-based learning systems has become an important topic for practitioners and academics. Based on DeLone and McLean's (2003) information systems success model and Goodhue and Thompson's (1995) task-technology fit model, this study proposes a blog-based learning system success model that contains seven variables: (1) knowledge and information quality, (2) system quality, (3) service quality, (4) reuse intention/system usage, (5) student satisfaction, (6) task-technology fit, and (7) learning performance. A set of propositions that describe the relationships between the seven focal variables is presented to enhance our understanding of how to use blog-based learning systems to enhance students' learning performance within a business education context. Theoretical and practical implications for the development and application of blog-based learning systems are then discussed. Highlights: This study proposes a blog-based learning system success model for the context of business education. The proposed model contains seven variables of blog-based learning system success. A set of propositions that describe the relationships between the seven focal variables is presented. The study provides some theoretical and practical implications for blog-based learning in a business education context.